Growth, secular stagnation and wealth preference - Yoshiyasu Ono (Osaka University, Institute of Social and Economic Research (ISER), 2015)
In 1960s - 1980s Japan enjoyed high economic growth. In the early 1990s, however, the growth rate drastically declined and thereafter Japan has been suffering secular stagnation. This paper proposes a dynamic macroeconomic model that can consistently explain such a drastic change in economic performance. Wealth preference plays an important role. In the early stage consumption grows at the same pace as productivity increases. Once consumption reaches a certain level, however, it deviates from the full-employment level and aggregate demand deficiency appears. After that the economic growth rate asymptotically approaches zero even if productivity keeps on increasing, and secular stagnation arises.
Keywords: E32; E13; 330; long-run stagnation; aggregate demand deficiency; wealth preference; fair wages; economic growth; Japan